Assessing Research Productivity of Agricultural Scientists of Professor Jayashankar Telangana State Agricultural University (Indian Journal of Extension Education, 2022)
Productivity is the quintessential indicator of efficiency in any system. Research productivity is the work outcome of the scientists in the area of research in a given period of time. The present study was conducted to assess the level of research productivity among the agricultural scientists of PJTSAU in the year 2021. A sample of 120 agricultural scientists including Scientists, Senior Scientists and Principal Scientists with a minimum of 3 years of experience in research after 2014, when the university PJTSAU was formed due to bifurcation of the state, were selected for the study purposively. An index to compute research productivity was developed with six indicators- Publication behaviour, Research activities undertaken, Research guidance and Mentoring, Awards and Recognition, Technologies/Knowledge generated and Intellectual Property Rights generated and was standardized by testing its validity and reliability. The majority of agricultural scientists had medium research productivity (47.5%) followed by very low (15.83%), low (15.00%), high (15.00%) and very high (6.67%). The lowest research productivity index score was 0.11 while highest was 0.88 which indicates that there is a scope to increase productivity among the agricultural scientists with low research productivity.